IMPLEMENTING ON INDEPENDENT STUDY STRATEGIES IN FOREIGN LANGUAGES TEACHING (Conferencea, 2024)
The success of learning significantly depends on the conditions that the teacher provides for students to learn actively and independently. Therefore, independent study, particularly in the context of foreign language teaching, has been extensively explored by scholars across various linguistic and educational domains. Notably, English, Russian, and Uzbek scholars have made substantial contributions to understanding and improving the methodologies and technologies used in independent language learning. The purpose of this article is about implementing and reflecting on independent study strategies in foreign language teaching, the main approaches to improving the methodology of independent study in teaching foreign languages.